Compensation of phase response changes in ultrasonic transducers caused by temperature variations. (March 2019) - Herdovics, Balint; Cegla, Frederic
One of the biggest challenges in structural health monitoring is the compensation of monitored data for environmental and operational conditions. In order to reliably estimate the changes in the structure, it is essential that the effects of environmental and operational conditions on the ultrasonic signal are compensated for before the signals are further analysed. The temperature-induced propagation speed change has the biggest effect on the ultrasonic signal and has been thoroughly investigated. This article investigates the subtler, yet also very important, changes in transducer output resulting from changes in the operating temperature. A compensation method is proposed which compensates for both the transducer phase response change and the wave's propagation speed change. A key practical feature of the presented compensation method is that it uses only the ultrasonic signal itself for compensation estimation and can be used for any type of ultrasonic wave regardless of the type of transducer. For demonstration purposes, in this article, the results are shown for zero-order torsional guided waves, acquired by a purpose-built electromagnetic acoustic transducer. For signals with a 41.5°C temperature difference, the proposed compensation method was able to reduce the effect of environmental and operational conditions by 20 dB further (7 dB at the tail of the echo) compared to standard methods. This results in a much higher sensitivity to defects in areas where strong reflections are received. Furthermore, for the presented measurement setup, the precision to which the temperature-dependent change in wave propagation speed could be estimated was improved by 15%.